Haunting experiences : ghosts in contemporary folklore - Goldstein, Diane E. (Utah State University Press, 2007)
"Ghosts and the supernatural appear throughout modern culture, in any number of entertainment, commercial, and other contexts. Popular media's commodified representations of ghosts can be quite different from what people believe about them, based on tradition or direct experience. Belief and tradition and the popular or commercial nevertheless continually feed off each other. They frequently share space in how people think about the supernatural. In Haunting Experiences, three well-known folklorists broaden the discussion of ghost lore by examining it from multiple angles in various modern contexts. Diane E. Goldstein, Sylvia Ann Grider, and Jeannie Banks Thomas take ghosts seriously. They draw on contemporary scholarship that emphasizes the basis of belief in experience and the usefulness of ghost stories. And they look closely at the narrative role of such lore in matters such as socialization and gender. Together, they unravel the complex mix of mass media, commodification, and popular culture that today puts old spirits into new contexts."--Publisher's description